A study of caloric restriction versus standard diet in overweight men with newly diagnosed prostate cancer: A randomized controlled trial. Issue 12 (15th June 2013) - Wright, Jonathan L.; Plymate, Stephen; D'Oria‐Cameron, Andrea; Bain, Carolyn; Haugk, Kathy; Xiao, Liren; Lin, Daniel W.; Stanford, Janet L.; McTiernan, Anne
ABSTRACT: INTRODUCTION: Obese men have an increased risk of prostate cancer (PCa)‐specific mortality. Potential mechanisms include insulin and related proteins. We investigate whether a short‐term caloric restriction diet in overweight/obese men with newly diagnosed PCa can lead to measurable changes in patient anthropometrics and insulin‐related proteins. METHODS: Overweight and obese PCa patients choosing active surveillance or radical prostatectomy were randomized to a 6‐week, caloric‐restricted diet or to continue their current diet. Changes from baseline to end of study in anthropometrics, dietary constituents and serum proteins (insulin, c‐peptide, IGF‐1, adiponectin, IGF‐BP3) were compared between the intervention and control groups using a Generalized Estimating Equation model. RESULTS: Nineteen patients were randomized to the intervention (N = 10) or control (N = 9) group. Men in the intervention group had a 1.7% (3.7 lbs) mean decline in weight versus 1.0% (2.0 lbs) in controls ( P < 0.05), and a reduced intake of calories, total and saturated fat, protein and starch (all P < 0.1 compared to controls). There was a significant difference ( P = 0.002) in mean serum IGFBP‐3 between the intervention (+2.8%) and control group (−6.9%). Other biomarkers changed with the diet intervention to a degree similar to previous weight loss studies but were not statistically significant compared with controls. CONCLUSION: In this small pilot study, a 6‐week caloric restricted diet in men with newly diagnosed PCa produced changes in weight, diet and serum proteins possibly related to prognosis. These results support larger‐scale trials testing longer‐term weight loss effects on potential PCa progression biomarkers. Prostate 73:1345–1351, 2013 . © 2013 Wiley Periodicals, Inc.